Climate Policies, Investments, and the Role of Elections - Achim Hagen; Gilbert Kollenbach (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study the interaction of climate policies and investments into fossil and renewable energy generation capacity under political uncertainty caused by democratic elections. We develop an overlapping generations model, where elected governments determine carbon taxation and green investment subsidies, and individuals make investments into fossil and renewable capacity. We find that some fossil investments become stranded assets if the party offering the higher carbon tax is unexpectedly elected. Green investment subsidies can be used by governments to bind the hands of their successor. By using the subsidy, the party in power can influence the capital stocks and, therefore, the climate policy of the following period to reduce or even avoid potentially stranded assets. With endogenous reelection probability, the impact on the capital stocks can also be used strategically to manipulate the reelection probabilities in favor of the party in power.
Keywords: D72; H23; Q54; Q58; 330; stranded assets; elections; fossil fuel; renewable energy; carbon tax; investment subsidy